2019
DOI: 10.1111/cas.13955
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor receptor modulator spermatogenesis‐associated protein 2 is a novel predictor of outcome in ovarian cancer

Abstract: Inflammation plays a crucial role in the pathogenesis of cancer with tumor necrosis factor‐α (TNF‐α) as a key mediator. Recently, spermatogenesis‐associated protein 2 (SPATA2) was identified as a TNF receptor modulator which is required for TNF‐induced inflammation and apoptosis. The available data on TNF‐α in ovarian cancer (OC) are inconsistent, and SPATA2 is completely uncharacterized in tumorigenesis. We analyzed expression of SPATA2 and TNFA by quantitative real‐time polymerase chain reaction in tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…SPATA2 has been identified as a bridging factor that regulates TNF-alphA-Induced necroptosis and is instrumental for TNF-induced cell death (Elliott et al, 2016;Kupka et al, 2016;Schlicher et al, 2016;Wagner et al, 2016;Schlicher et al, 2017). SPATA2 ensures normal secretory function of Sertoli cells (Zhao et al, 2017) and has recently been identified as a novel predictor in ovarian cancer outcome (Wieser et al, 2019). While SPATA2 has been linked to ubiquination (Schlicher et al, 2016), post-translational deimination has not been invesigated.…”
mentioning
confidence: 99%
“…SPATA2 has been identified as a bridging factor that regulates TNF-alphA-Induced necroptosis and is instrumental for TNF-induced cell death (Elliott et al, 2016;Kupka et al, 2016;Schlicher et al, 2016;Wagner et al, 2016;Schlicher et al, 2017). SPATA2 ensures normal secretory function of Sertoli cells (Zhao et al, 2017) and has recently been identified as a novel predictor in ovarian cancer outcome (Wieser et al, 2019). While SPATA2 has been linked to ubiquination (Schlicher et al, 2016), post-translational deimination has not been invesigated.…”
mentioning
confidence: 99%
“…29,30 Our results in company with previous findings highly suggested that SPATA2 is tumor suppressing. However, SPATA2 was recently reported to be upregulated and its upregulation was associated with poor prognosis in ovarian cancer 31 and endometrial cancer. 32 The differences might be possibly because of the different types of cancer investigated of these studies and this also indicated that the role of SPATA2 in cancer might be context-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α pathway modulates immune responses ( Swann et al, 2008 ). TNF-α and IL-1β induced SPATA2 expression in ovarian cancer cells and that increased SPATA2 expression was associated with poor prognosis of ovarian cancer patients ( Wieser et al, 2019 ). Our study suggested SPATA2 expression is also associated with poor prognosis of HNSCC patients.…”
Section: Discussionmentioning
confidence: 99%